Automated flow injection method for the high precision determination of drift tube ion mobility collision cross sections. Issue 7 (15th March 2018) - Nichols, Charles M.; May, Jody C.; Sherrod, Stacy D.; McLean, John A.
Abstract : This work presents a fully automated method to generate absolute Collision Cross Sections for annotated libraries. Abstract : The field of ion mobility-based omics studies requires high-quality collision cross section (CCS) libraries to effectively utilize CCS as a molecular descriptor. Absolute CCS values with the highest precision are obtained on drift tube instruments by measuring the drift time of ions at multiple drift voltages, commonly referred to as a 'stepped field' experiment. However, generating large scale absolute CCS libraries from drift tube instruments is time consuming due to the current lack of high-throughput methods. This communication reports a fully automated stepped-field method to acquire absolute CCS on commercially available equipment. Using a drift tube ion mobility-mass spectrometer (DTIM-MS) coupled to a minimally modified liquid chromatography (LC) system, CCS values can be measured online with a carefully timed flow injection analysis (FIA) experiment. Results demonstrate that the FIA stepped-field method yields CCS values which are of high analytical precision (<0.4% relative standard deviation, RSD) and accuracy (≤0.4% difference) comparable to CCS values obtained using traditional direct-infusion stepped-field experiments. This high-throughput CCS method consumes very little sample volume (20 μL) and will expedite the generation of large-scale CCS libraries to support molecular identification within global untargeted studies.